Elbow joint proprioceptive sense in total arm-type brachial plexus injured patients after neurotization: A preliminary study - Therdsak Homsreprasert (2018)
© 2014, Medical Association of Thailand. All Rights Reserved. Background: Joint proprioceptive sense is a special sense, which is composed of joint kinesthesia and joint reposition sense. Cells that receive proprioceptive sensation normally can be found in skin, soft tissue, tendon, and muscle around the joint. Their function coordinates with visual sensation and sensation from the vesicular organ to acknowledge position of the body. The proprioceptive sense provides information for motion in the dark, the ability to manipulate objects out of view, and protective sensation.There are several reports on the recovery of motor function after neurotization in brachial plexus injured patients. To date, there has been no study relating to recovery of proprioceptive sensation in brachial plexus injured patients after neurotization. Objective: To study elbow joint position sense or proprioceptive sense in total arm-type brachial plexus injured patients after neurotization. Material and Method: The present study was undertaken at a major academic tertiary care center in Bangkok, Thailand from October 2012 to January 2014. The design of this prospective cohort study included seven total arm-type brachial plexus injured patients before neurotization and seven total arm-type brachial plexus injured patients after neurotization, the latter seven of whom experienced recovery of motor power of biceps to at least MRC III. All patients were examined using the CONTREX dynamometer to assess elbow joint position sense. Patients were asked to recognize elbow joint position sense at two different target angles-mid-range and end-range. The differences between the actual angles and the angles perceived by the patients were calculated and statistically analyzed using the Wilcoxon signed ranks test. Results: There were no statistically significant differences in age or side of injury between the two groups of patients. In the pre-neurotization group, there was a statistically significant difference between the injured side and normal side in mid-range (50%) and end-range (90%) target angles. However, elbow joint position sense in the after neurotization group (with MRC III motor recovery) showed no statistically significant difference between the injured side and the normal side in mid-range (50%) and end-range (90%) target angles. Conclusion: Total arm type brachial plexus injured patients recover proprioceptive sense in the elbow after neurotization.